O conceito de repetição na psicanálise freudiana: ressonâncias clínicas na re-elaboração simbólica do repetido - Barbosa Neto, Esperidião (2010)
Repetition is one of the fundamental concepts of psychoanalysis. The compulsive character of repetition is linked to the death drive: pure quantity, affection without representations, designed at random, furiously. The subject is compelled against his will, re-edit new editions of traumatic events. The recurrence of this suffering, in the transfer, took effect healing. For Freud, the treatment is the use of the word: both the speech of the analyzed and the analyst, focuses on feelings not represented, silenced, but untamed since the trauma. The metaphorical interpretation is able to name the unspeakable. The subject re-signifies the emotional experience as the verbalizations, the repetitive acts lose consistency. In this research, theoretical, we worked on the concept of repetition from Freud s theory, linking it to the treatment. Contributions from other psychoanalytic investigators and clinical illustrations were used in order to characterize the clinical transfer as where the repetition compulsion can be treated. It is, as a result of research, a return to the clinic. The aim is to advance the examination of what has been done so far, typical of scientific development, and that was the work of Freud.